2008
DOI: 10.1101/gad.479308
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear receptor tailless is required for neurogenesis in the adult subventricular zone

Abstract: Supplemental material is available at http://www.genesdev.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
181
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(196 citation statements)
references
References 31 publications
11
181
2
2
Order By: Relevance
“…In that study, Tlx-null cells isolated from mutant adult mouse brains presented proliferation defects that were rescued by reintroducing Tlx expression. The essential role of mouse Tlx in activating neurogenesis from adult NSCs has been validated by several studies [35,49]. Zhang et al further showed that Tlx is indispensable for stem-cell proliferation in the adult mouse brain and for certain cognitive functions such as spatial learning [36].…”
Section: Roles Of Tlx Homologues In the Regulation Of Nscs And Brain mentioning
confidence: 96%
See 2 more Smart Citations
“…In that study, Tlx-null cells isolated from mutant adult mouse brains presented proliferation defects that were rescued by reintroducing Tlx expression. The essential role of mouse Tlx in activating neurogenesis from adult NSCs has been validated by several studies [35,49]. Zhang et al further showed that Tlx is indispensable for stem-cell proliferation in the adult mouse brain and for certain cognitive functions such as spatial learning [36].…”
Section: Roles Of Tlx Homologues In the Regulation Of Nscs And Brain mentioning
confidence: 96%
“…At the embryonic stage, Tlx expression presents a graded pattern in the telencephalon along the dorsalventral axis with a high level in the dorsal-lateral region and a low level in the ventral-medial region [33]. Tlx is also expressed in postnatal NSCs and may activate neurogenesis in the subventricular zone of the lateral ventricle based on the findings that Tlx mutant brains have severely reduced hippocampal dentate gyri and greatly expanded lateral ventricles in adult mice [34][35][36]. Tlx expression is also detectable in the ventricular zone enriched with NSCs at the postnatal stage [30,37,38].…”
Section: Tlx Expression Its Targets and Related Signal Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Tlx is specifically expressed in the adult brain in both the adult hippocampus and SVZ (Monaghan et al, 1995;Roy et al, 2004;Shi et al, 2004) and may mark the relatively quiescent population of SVZ stem cells (Liu et al, 2008). NSCs isolated from young adult mice with a constitutive deletion of Tlx show defects in selfrenewal in vitro and in vivo and spontaneous differentiation along the astrocytic lineage due to TLX-mediated repression of pro-astrocytic genes (Shi et al, 2004).…”
Section: Foxo Transcription Factors In Adult Stem Cells: Integrating mentioning
confidence: 99%
“…NSCs isolated from young adult mice with a constitutive deletion of Tlx show defects in selfrenewal in vitro and in vivo and spontaneous differentiation along the astrocytic lineage due to TLX-mediated repression of pro-astrocytic genes (Shi et al, 2004). Inducible deletion of Tlx in adults reduces adult neurogenesis (Liu et al, 2008;Zhang et al, 2008), thus underscoring a role for TLX in adult NSCs independent of its function in development. The role for TLX in selfrenewal and differentiation of NSCs has been linked to its interactions with chromatin modifiers HDAC3, HDAC5 and histone demethylase LSD1 (Shi et al, 2004).…”
Section: Foxo Transcription Factors In Adult Stem Cells: Integrating mentioning
confidence: 99%